TRANSMISI MULTICAST DATA RADAR PADANG – PEKANBARU SEBAGAI MEDIA PEMBELAJARAN DI POLTEKBANG SURABAYA - Erdiyansyah Rafif falah; Yuyun Suprapto; Wiwid Suryono (Journal of Public Transportation Community, 2022)
Multicast Radar data is a concept in modern radar systems that aims to efficiently transmit and receive data from multiple receivers (receiver) simultaneously. Radar is an important technology in the surveillance and monitoring of various areas, both in military and civilian applications. In situations where the data from the radar must be accessed by multiple receivers, use of the technique multicast be an efficient choice for sending the data to multiple destinations simultaneously. The method used in this study uses the ADDIE development method. The ADDIE method makes it easier to make transmissions Multicast Radar data Padang - Pekanbaru using the method tunnel in tunnel.This transmission consists of components hardware and software as a material in transmission planning Multicast Radar data Padang – Pekanbaru uses hardware laptop or PC and software virtualbox, winbox64.exe, ASTModoS.exe, wireshark. The data analysis technique carried out by the author is assessing quality of Service (QoS) of the Radar Data transmission design that has been made by the author.